1955
DOI: 10.1104/pp.30.2.93
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Sap in Tall Grapevines.

Abstract: The common northern grapevine (Vitis labrusca L.) grows rather abundantly in the wooded area around Woods Hole, Massachusetts. It frequently grows as a liana, climbing high in various trees, and attaining heights of 17 to 18 meters. In the winter the vessels of the stem and branches are filled with gas and usually contain no sap. With the warm weather in April and MIay, and before the leaves are outs the vines become full of sap which drips out from the slightest cut in the wood of stem or twigs. The vessels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0
1

Year Published

1958
1958
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 19 publications
4
62
0
1
Order By: Relevance
“…This happens whether wvater freezes in bulk or in glass capillaries (27). It has been shown that the sap of the grapevine is fully saturated with dissolved atmiiosplheric nitrogen (28), and the same very likely holds also for other species. One must, therefore, assume that gas bubbles are formed whelnever freezing takes place in sap-filledl vessels and tracheids, andl a great many of these wvould henice becolme emptie(d aild eliminiatedl for the transl)ort system, wrere the sap under tension at the time of thawing.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…This happens whether wvater freezes in bulk or in glass capillaries (27). It has been shown that the sap of the grapevine is fully saturated with dissolved atmiiosplheric nitrogen (28), and the same very likely holds also for other species. One must, therefore, assume that gas bubbles are formed whelnever freezing takes place in sap-filledl vessels and tracheids, andl a great many of these wvould henice becolme emptie(d aild eliminiatedl for the transl)ort system, wrere the sap under tension at the time of thawing.…”
mentioning
confidence: 87%
“…The only mechanism which might conceivably repair suich breaks, would be a sap pressure higlh enough to redlissolve the gas. In the case of the grapevine, which empties its vessels during the winter, the root pressuire in the sprinlgtime is so high that it nmay readily refill the conducting system (28). But such pressures are at present known only in a few hardwood species (3,8,13,17,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scholander et al (7) showed this to be true in a leafless grapevine. In a plant with leaves, the water column is usually under tension, but nevertheless a static column should still show a hydrostatic gradient if the tube model is applicable.…”
Section: Iamentioning
confidence: 99%
“…This has been a result of the creation of new techniques based on the detection of sounds (Milburn, 1973) or, more reliably, ultrasounds (Tyree and Dixon, 1983) (Scholander et al, 1955;Hammel, 1967;Sucoff, 1969) using an instrument similar to the one described by Sandford and Grace (1985), slightly modified. Freezing of stem tissues was monitored with thermocouple sensors (type T) connected to a strip chart recorder.…”
Section: Introductionmentioning
confidence: 99%